Partisipasi Masyarakat Desa dalam Melakukan Pengelolaan Sampah - Pangestu, Wendy Essa; Nurani, Permata Cakrawala; Tri Amanda, Yusriyyah; Anjani, Diana Putri; Ihsani, Hanna Rulandari; Hadiyanto, M. Faiz; Eksan, Muhammad Pratama; Rahmayanti, Devi (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2022)
Gede Pangrango Village is one of the tourist villages that has natural beauty that makes many people interest to visit. But behind the beauty there are problems that make the natural beauty itself reduced due to waste management that has not been maximized. To reduce environmental damage, it is necessary to have community participation in waste management. This study aims to determine community participation in waste management with a waste management system and to find out the benefits resulting from the existence of waste management through several programs. This research is a type of field research or field research. This research is a qualitative descriptive study. Methods of data collection in this study using observation, interviews, and documentation. Participants used in this study is representative of the Environment Agency, the village head, head of the local (RW), youth clubs and organizations in the village. The study states that waste management still in the unfavorable category, this is due to many factors: the lack of land for the construction of temporary shelters, facilities and infrastructures are not good enough and the level of public awareness is still low about the importance to manage waste properly.